An enantioselective Bronsted acid catalyzed enamine Mannich reaction. - Tillman, A; Dixon, D (2007)
An enantioselective Brønsted acid catalyzed Mannich reaction between acetophenone derived enamines and N-Boc imines has been developed. Simple diol (S)-H(8)-BINOL has been identified as the optimal catalyst, to afford versatile beta-amino aryl ketones in good yield and enantiomeric excess.